2014
DOI: 10.1634/theoncologist.2013-0339
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate Is an Easy Predictor of Venous Thromboembolism in Cancer Patients Undergoing Platinum-Based Chemotherapy

Abstract: Background. Reduced estimated glomerular filtration rate (eGFR) has been associated with increased venous thromboembolism (VTE) risk in the general population. VTE incidence significantly increases in cancer patients, especially those undergoing chemotherapy. Despite the evidence that a substantial number ofcancer patients have unrecognized renal impairment, as indicated by reduced eGFR in the presence of serum creatinine levels within the reference value, chemotherapy dosage is routinely adjusted for serum cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Finally, a recent study investigating real-world features associated with cancer-related VTE showed that serum creatinine can be considered an independent indicator of increased VTE risk during platinum-based chemotherapy [154], confirming previous findings demonstrating that estimated glomerular filtration rate is associated with an increased VTE risk in cancer outpatients treated with platinum compounds, even under normal serum creatinine values [155].…”
Section: Vte Biomarkerssupporting
confidence: 75%
“…Finally, a recent study investigating real-world features associated with cancer-related VTE showed that serum creatinine can be considered an independent indicator of increased VTE risk during platinum-based chemotherapy [154], confirming previous findings demonstrating that estimated glomerular filtration rate is associated with an increased VTE risk in cancer outpatients treated with platinum compounds, even under normal serum creatinine values [155].…”
Section: Vte Biomarkerssupporting
confidence: 75%
“…Interestingly, reduced estimated glomerular filtration rate even under normal serum creatinine values has been shown to associate with an increased risk of VTE. 39 …”
Section: Discussionmentioning
confidence: 99%
“…The use of a general screening strategy is appealing, because it could provide the opportunity for prophylactic treatment, reducing the event rates in at-risk cancer patients. 100 Indeed, one multivariate analysis reported that eGFR (<90 mL/ min/1.73 m²) was the only independent predictive factor of VTE occurrence in a cohort of 322 consecutive patients with primary or relapsing/recurrent solid cancers who were receiving different standard combinations of platinum-based regimens. 100 The authors suggested that pretreatment eGFR could serve as a simple and cost-effective predictor of venous thromboembolic events in cancer patients.…”
Section: Discussionmentioning
confidence: 99%